The Pre-History of the English Laws Act 1858: Mcliver v Macky (1856) - Williams, David V (Victoria University of Wellington Law Review, 2010)
The English Laws Act 1858 declared the reception date for the arrival of English law and statutes of general application in New Zealand to be 14 January 1840. This Act was passed because the New Zealand Supreme Court had decided the Wills Act 1837 (UK) did not apply in New Zealand. New Zealand was annexed to the British Empire as a dependency of New South Wales with a reception date in 1825 or 1828. The Supreme Court case that so decided was McLiver v Macky (1856). The New Zealand Law Foundation's 'Lost Cases Project' ascertained that this judgment was fully reported in an Auckland newspaper – The Southern Cross. This article examines the facts of the case and the reasoning of Acting Chief Justice Stephen as to the basis for British sovereignty in New Zealand and the application of English law to British subjects here.